Public perceptions of flood management schemes in the UK - D'Souza, Mikaela (2020)
This research investigated the public’s perceptions of flood management schemes within the UK. Generally, the research considered whether there was an overall preference for natural flood management schemes or hard-engineering (‘grey-infrastructure’) schemes. The research explored individuals’ perceptions with regard to three main characteristics; the appearance, the effectiveness and the benefits to wildlife and how these impacted on their view of water management systems. Additionally, individuals’ underlying values (tied to the guiding principles in their lives) were established and compared with the individuals’ perception of flood management options. This is a novel idea, as there has been little research associated with gaining an understanding and utilising the individuals’ values specifically to assess rivers and flood management. Following this, the research considered whether there are other variables such as socio-demographics which would contribute to, and impact on, public perceptions. The methodology employed during this research included a questionnaire administered online, the Q-methodology and interviews conducted using the Projected Augmented Reality Model (PARM) as an external stimulus. The interviews conducted for both the PARM and the Q-method were used as supplementary, qualitative data to support the quantitative statistical analysis. The overall findings highlighted a preference for natural flood management with regard to appearance, effectiveness and benefits to wildlife. Furthermore, “Self-Transcendence”, “Openness to Change” and “Conservatism” value orientations were significantly associated with flood management preferences. In contrast, “Self-Enhancement” values were found to have no relationship with the flood management schemes. Finally, individuals’ preferences for flood management systems increased with higher levels of education, indicating that increasing public knowledge in this area would be likely to lead to greater support for management scheme usage.